2004
DOI: 10.1128/aem.70.2.1160-1168.2004
|View full text |Cite
|
Sign up to set email alerts
|

Integron Diversity in Heavy-Metal-Contaminated Mine Tailings and Inferences about Integron Evolution

Abstract: Integrons are horizontal gene transfer (HGT) systems containing elements necessary for site-specific recombination and expression of foreign DNA. The overall phylogenetic distribution of integrons and range of genes that can be transferred by integrons are unknown. This report contains an exploration of integrons in an environmental microbial community and an investigation of integron evolution. First, using cultureindependent techniques, we explored the diversity of integrons and integron-transferred genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
105
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 57 publications
9
105
0
1
Order By: Relevance
“…Fluit and Schmitz (2004) resistance (Bass et al, 1999;Sorum et al, 2003). A recent study (Nemergut et al, 2004) has shown evidence of a gene cassette encoding nitroaromatic catabolism, a group of compounds associated with mining activity, this highlights the fact that other selective pressures other than antibiotics may also co-select for resistance genes. The process by which a gene becomes a movable cassette is not understood; however, it has been proposed that the 59-base element is added as a transcription terminator to an RNA gene transcript that is subsequently converted into DNA by a hypothetical reverse transcriptase (Recchia and Hall, 1995).…”
Section: Mechanisms Of Horizontal Gene Transfermentioning
confidence: 99%
“…Fluit and Schmitz (2004) resistance (Bass et al, 1999;Sorum et al, 2003). A recent study (Nemergut et al, 2004) has shown evidence of a gene cassette encoding nitroaromatic catabolism, a group of compounds associated with mining activity, this highlights the fact that other selective pressures other than antibiotics may also co-select for resistance genes. The process by which a gene becomes a movable cassette is not understood; however, it has been proposed that the 59-base element is added as a transcription terminator to an RNA gene transcript that is subsequently converted into DNA by a hypothetical reverse transcriptase (Recchia and Hall, 1995).…”
Section: Mechanisms Of Horizontal Gene Transfermentioning
confidence: 99%
“…Under the selective pressure of intensive antibiotic use, class 1 integrons have used the cassette metagenome to engineer the phenotype of multiple antibiotic resistance (Hall & Collis, 1998;Rowe-Magnus et al, 2001). Examination of genome sequence data and targeted environmental surveys have shown that integrons are diverse and present in~5 % of bacterial genomes (Nemergut et al, 2004;Nield et al, 2001;Rowe-Magnus et al, 2001). Given the size of the gene cassette reservoir and the relative frequency of integrons, we might expect that the integron-gene cassette system has also engineered phenotypes other than antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently thrity-two unique integron integrase genes available in GeneBank and various sequencing projects, an eight-fold increase in the past 3 years. 8) However only 3 classes of integrons are to date the most extensively studied and clinically significant, defined class 1, 2 and 3 integrons. The gene cassettes found in these integrons are much more variable; more than 60 different gene cassettes have been described, including gene cassettes conferring resistance to aminoglycosides, penicillins, cephalosporins, carbapenems, trimethoprim, chloramphenicol, rifampin, erythromycin, and quaternary ammonium compounds.…”
Section: Introductionmentioning
confidence: 99%